Pengembangan Media Permainan Ular Tangga untuk Mengembangkan Keterampilan Sosial dan Regulasi Emosi Anak Usia Dini - Ari Rahmi Hasfaraini; Kusumawati Kusumawati (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
The development of social skills and emotional regulation in early childhood requires stimulation that aligns with children's play-based learning characteristics. This study aimed to develop an educational snakes-and-ladders game as a learning medium to support the development of social skills and emotional regulation among children aged 4–6 years. The research employed a Research and Development approach using the ADDIE model, encompassing the Analyze, Design, and Development phases. The participants were children from Bintang Kecil Playgroup in Tanjung Palas, and data were collected through material expert validation, media expert validation, and teacher response questionnaires. The results indicated that the developed medium achieved high feasibility scores from material experts (87.85%), media experts (84.34%), and teachers (92.58%). Limited trials demonstrated that children were enthusiastic, actively interacted with peers, and were able to follow game rules. The novelty of this study lies in integrating social skills and emotional regulation stimulation into an educational snakes-and-ladders game. The medium is considered feasible as a play-based learning alternative and contributes to the development of social-emotional learning media for early childhood education.